PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION (GI) TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL ELAJAR BIOLOGI SISWA KELAS X SMA NEGERI 4 SURAKARTA TAHUN PELAJARAN 2011/2012 - Primarinda, Ikha; Maridi, Maridi; Marjono, Marjono (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? The aim of the research was to know the influence of Group Investigation type (GI) of cooperative learning model toward science process skill and biology learning achievement of X degree students at SMA Negeri 4 Surakarta in the academic year of 2011/2012. The methodology of the research was quasi-experimental with quantitative approach. The research designs were post-test only control group by using experimental class (the implementation of Group Investigation (GI) of cooperative learning model) and control class (conventional learning). The population of this research is all of X degree students at SMA Negeri 4 Surakarta in 2011/2012 academic year. The sample was taken by using cluster random sampling technique, with the result that XB class as experimental group and XA class as control group. The technique of collecting data used test, observation paper and the school document. The data was analyzed by using t-test. This research concluded that Group Investigation type (GI) of cooperative learning model was significantly effective toward science process skill and biology learning achievement of X degree students at SMA Negeri 4 Surakarta in the academic year of 2011/2012. Keywords: cooperative learning, Group Investigation, Science process skill, biology learning achievement.